2006
DOI: 10.1038/ni1383
|View full text |Cite
|
Sign up to set email alerts
|

Smad6 negatively regulates interleukin 1-receptor–Toll-like receptor signaling through direct interaction with the adaptor Pellino-1

Abstract: Transforming growth factor-beta1 (TGF-beta1) is a potent cytokine with pleiotropic effects, including anti-inflammatory activity. Here we show that the signaling protein Smad6 bound to Pellino-1, an adaptor protein of mammalian interleukin 1 receptor (IL-1R)-associated kinase 1 (IRAK1), and thereby promoted TGF-beta-mediated anti-inflammatory effects. Smad6-Pellino-1 interaction abrogated signaling mediated by a complex of IRAK1, Pellino-1 and adaptor protein TRAF6 that formed after stimulation by IL-1beta tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 55 publications
3
138
0
Order By: Relevance
“…Intriguingly, some studies have demonstrated that members of the Pellino family can be targeted by regulatory strategies to suppress TLR signalling [33,44,49]. Indeed, the role of Pellino3 as a direct negative regulator of innate immune signalling has already been described [33] (Figure 4a).…”
Section: Pellino Proteins As Novel Targets For Negative Regulation Ofmentioning
confidence: 98%
See 4 more Smart Citations
“…Intriguingly, some studies have demonstrated that members of the Pellino family can be targeted by regulatory strategies to suppress TLR signalling [33,44,49]. Indeed, the role of Pellino3 as a direct negative regulator of innate immune signalling has already been described [33] (Figure 4a).…”
Section: Pellino Proteins As Novel Targets For Negative Regulation Ofmentioning
confidence: 98%
“…However, other reports have failed to detect any basal interactions between overexpressed MyD88 and Pellino proteins [37,47]. Many groups have described associations of each of the Pellino proteins with TRAF6 and these interactions are strongly promoted by IL-1R signalling [33,36,37,41,44,47]. The nature of these interactions remains to be defined with no available data to date to indicate whether Pellino proteins interact directly with TRAF-6 or indirectly as part of a larger protein complex.…”
Section: Pellino Proteins Interact With Other Tlr and Il1-r Signallinmentioning
confidence: 99%
See 3 more Smart Citations